An Open-Label, Randomized Study of the Impact on Insulin Sensitivity, Lipid Profile and Vascular Inflammation by Treatment with Lopinavir/Ritonavir or Raltegravir in HIV-Negative Male Volunteers. Issue 2 (February 2017) - Randell, Paul; Jackson, Akil; Milinkovic, Ana; Boffito, Marta; Moyle, Graeme
Background: We aimed to measure the effect of raltegravir (RAL) on insulin sensitivity and surrogates of cardiovascular risk in healthy HIV-seronegative volunteers compared to that of lopinavir/r (LPV/r), a positive control. Methods: An open-label, two phase crossover study in HIV-negative male subjects randomized 1:1 to receive either 2 weeks of LPV/r followed by a 2-week washout period and 2 weeks of RAL, or RAL initially followed by LPV/r. A hyperinsulinaemic euglycaemic clamp was performed prior to and following each 2-week dosing phase. Fasting samples for lipids, adiponectin, leptin, vascular inflammatory biomarkers and CD36 were also taken. Results: A total of 16 subjects completed the study. At the baseline visit the mean insulin-stimulated glucose disposal per unit insulin (M/I) was 7.97 and 8.30 for LPV/r and RAL, respectively. The mean (sem ) percentage change from baseline was -16.10% (3.84) after 2 weeks of LPV/r and -0.43% (4.83) after 2 weeks of RAL. Absolute M/I was 25% lower for LPV/r than for RAL ( P =0.001). Triglycerides and total cholesterol rose significantly with LPV/r (+0.5 mmol/l, P =0.002 and +0.4 mmol/l, P <0.0001), but were unchanged with RAL. Proathrogenic lipid subfractions of low-density lipoprotein (LDL) cholesterol increased with LPV/r and were unaffected with RAL. LDL peak and mean particle diameter and LDL I significantly decreased with LPV/r ( P <0.05), and trend of increased LDL III was detected. High-sensitivity C-reactive protein declined with RAL (-0.2 mg/l, P =0.043) but was elevated after LPV/r (+0.25 mg/l, P =0.03). Conclusions: RAL was not associated with measurable change in glycaemic, metabolic or inflammatory effects.